Courseware for telework and training - Marcos, Adérito (2012)
This article reports on a CCG's project which aimet at developing an interactive course on telework issues, focusing especially on technology, solutions, strategies and recommendations for its integration in daily life. This follows a growing demand coming from companies that start to see telework and the ICTs as valuable tools for cutting costs and improving their organization and work processes. Thus, the target audience of this course are IT professionals and SMEs.